Feasibility and Effect of Physiological-Based CPAP in Preterm Infants at Birth - Martherus, Tessa; Kuypers, Kristel L. A. M.; Böhringer, Stefan; Dekker, Janneke; Witlox, Ruben S. G. M.; Hooper, Stuart B.; Pas, Arjan B. te (Frontiers in Pediatrics, 2021)
Background Preterm infants are commonly supported with 5-8 cmH2O CPAP. However, animal studies demonstrate that high initial CPAP levels (12-15 cmH2O) which are then reduced (termed physiological based (PB)-CPAP), improve lung aeration without adversely affecting cardiovascular function. We investigated the feasibility of PB-CPAP and the effect in preterm infants at birth. Methods Preterm infants (24-30 weeks gestation) were randomized to PB-CPAP or 5-8 cmH2O CPAP for the first 10 min after birth. PB-CPAP consisted of 15 cmH2O CPAP that was decreased when infants were stabilized (heart rate ≥100 bpm, SpO2 ≥85%, FiO2 ≤0.4, spontaneous breathing) to 8 cmH2O with steps of ~2/3 cmH2O/min. Primary outcomes were feasibility and SpO2 in the first 5 min after birth. Secondary outcomes included physiological and breathing parameters and short-term neonatal outcomes. Planned enrollment was 42 infants. Results The trial was stopped after enrolling 31 infants due to a low inclusion rate and recent changes in the local resuscitation guideline that conflict with the study protocol. Measurements were available for analysis in 28 infants (PB-CPAP n=8, 5-8 cmH2O n=20). There protocol deviations in the PB-CPAP included one infant receiving 3 inflations with 15 cmH2O PEEP and two infants in which CPAP levels were decreased faster than described in the study protocol. In the 5-8 cmH2O CPAP group, three infants received 4, 10 and 12 cmH2O CPAP. During evaluations, caregivers indicated that the current PB-CPAP protocol was difficult to execute. The SpO2 in the first 5 min after birth was not different (61 (49-70) vs 64 (47-74), p=0.973). However, infants receiving PB-CPAP achieved higher heart rates (121 (111-130) vs 97 (82-119) bpm, p=0.016) and duration of mask ventilation was shorter (0:42 (0:34-2:22) vs 2:58 (1:36-6:03) min, p=0.020). Infants in the PB-CPAP group required 6:36 (5:49-11:03) min to stabilize, compared to 9:57 (6:58-15:06) min in the 5-8 cmH2O CPAP group (p=0.256). There were no differences in short-term outcomes. Conclusion Stabilization of preterm infants with PB-CPAP is feasible but tailoring CPAP appeared challenging. PB-CPAP did not lead to higher SpO2 but increased heart rate and shortened the duration of mask ventilation, which may reflect faster lung aeration.